The molecules of life : physical and chemical principles - Kuriyan, John; Konforti, Boyana; Wemmer, David (New York : Garland Science, 2013)
'Key to making future advances in the areas of biochemistry and molecular medicine is a new generation of molecular biologists and biochemists who are able to harness the tools and insights of physics and chemistry to exploit the emergence of genomic and systems-level information in biology.The basic ideas of energy, entropy, equilibrium thermodynamics, transport processes and reaction kinetics are closely related to exciting issues in contemporary biology, such as protein folding, chaperones and prion diseases, DNA polymerase and ribosome fidelity, DNA recognition, drug design, signal transduction, ion channel function, motor protein action and the versatility of enzyme mechanism. Providing this physical chemistry and biochemical foundation is The'Molecules of Life', a new undergraduate textbook for undergraduate students majoring in biology or pre-med. It deepens our understanding of how life functions by illuminating the physical principles underpinning biological phenomena'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Molecular biology -- Methods; Biochemical Processes -- physiology; Genomics -- methods